A multicentre randomised trial comparing octreotide and injection sclerotherapy in the management and outcome of acute variceal haemorrhage. Issue 4 (1st October 1997) - Jenkins, S A; Shields, R; Davies, M; Elias, E; Turnbull, A J; Bassendine, M F; James, O F W; Iredale, J P; Vyas, S K; Arthur, M J P; Kingsnorth, A N; Sutton, R
Abstract : Background —Few studies have compared vasoactive drugs with endoscopic sclerotherapy in the control of acute variceal haemorrhage. Octreotide is widely used for this purpose, but its value remains undetermined. Aims —To compare octreotide with endoscopic sclerotherapy for acute variceal haemorrhage. Patients —Consecutive patients with acute variceal haemorrhage. Methods —Patients were randomised at endoscopy to receive either a 48 hour intravenous infusion of 50 μg/h octreotide (n=73), or emergency sclerotherapy (n=77). Results —Overall control of bleeding and mortality was not significantly different between octreotide (85%, 62 patients) and sclerotherapy (82%, 63 patients) over the 48 hour trial period (relative risk of rebleeding 0.83; 95% confidence interval (CI) 0.38 to 1.82), irrespective of Child's grading or active bleeding at endoscopy. One major complication was observed in the sclerotherapy group (aspiration) and two in the octreotide group (pulmonary oedema, severe paralytic ileus). During 60 days of follow up there was an overall trend towards an increased mortality in the octreotide group which was not statistically significant (relative risk of dying at 60 days 1.91, 95% CI 0.97 to 3.78, p=0.06). Conclusions —The results of this study indicate that intravenous octreotide is as effective as injection sclerotherapy in the control of acute variceal bleeding, but further controlled trials are necessary to evaluate the safety of this treatment.